A General Way to Spiro-Annulated 2-Benzoxepines via Rh2(esp)2-Catalyzed [5+2] Cycloaddition of Diazo Arylidene Succinimides to Ketones - Vepreva, Anastasia; Kantin, Grigory; Krasavin, Mikhail; Dar’in, Dmitry (Synthesis, 2022)
The formation of spirocyclic 2-benzoxepines by Rh2(esp)2-catalyzed decomposition of diazo arylidene succinimides in the presence of ketones was investigated. This transformation, which is a formal [5+2] cycloaddition of styryl rhodium carbenes to the carbonyl group, occurs in high yields under mild conditions, with high carbonyl substrate tolerance and diastereoselectivity. The developed general method opens access to rare spiro (hetero)cyclic scaffolds with great potential in drug discovery.
Keywords: spirocyclic scaffold; 2-benzoxepines; cyclic α-diazocarbonyl compounds; conjugated carbonyl ylide; electrocyclization